AKTIVITAS RELIGI DI SITUS CANDI PERTAPAN KABUPATEN BLITAR PADA MASA KADIRI HINGGA MAJAPAHIT - M Satok Yusuf; I Wayan Srijaya; Coleta Palupi Titasari (Berkala Arkeologi Sangkhakala, 2021)
Society in the Classical period had view that most sacred buildings were erected in the highlands, such as an Mount Pegat, Blitar Regency. This study seeks to reveal the religious activities that occured at Pertapan Temple Site on Mount Pegat from the Kadiri to Majapahit Kingdom, along with the community’s conception of the mountain. The method used in this study includes data collection in the form of observations and interviews, as well as qualitative descriptive analysis through the help of classification, comparison, and contextual analysis. Semiotic theory is used to assist the analysis. The result of this study indicate that the sacred building at the Pertapan Temple site is use as a place of worship for Sang Hyang Kabuyutan in Subhasita in 1120 Saka, the pendharmaan temple of King Wisnuwarddhana in 1202 Saka, and place of worship of Dewaraja Wisnuwarddhana in 1237 Saka. the community views Mount Pegat as a holy place, because it has several features, such as according to the criteria for a holy place, the location is on the connecting route between Kadiri and Singhasari and Mount Kelud with the South Lime Mountains.